Dysbiotic lung microbial communities of neonates from allergic mothers confer neonate responsiveness to suboptimal allergen - Bloodworth, Jeffery C.; Hoji, Aki; Wolff, Garen; Mandal, Rabindra K.; Schmidt, Nathan W.; Deshane, Jessy S.; Morrow, Casey D.; Kloepfer, Kirsten M.; Cook-Mills, Joan M. (Frontiers in Allergy, 2023)
In humans and animals, offspring of allergic mothers have increased responsiveness to allergens. This is blocked in mice by maternal supplementation with α-tocopherol (αT). Also, adults and children with allergic asthma have airway microbiome dysbiosis with increased Proteobacteria and may have decreased Bacteroidota. It is not known whether αT alters neonate development of lung microbiome dysbiosis or whether neonate lung dysbiosis modifies development of allergy. To address this, the bronchoalveolar lavage was analyzed by 16S rRNA gene analysis (bacterial microbiome) from pups of allergic and non-allergic mothers with a basal diet or αT-supplemented diet. Before and after allergen challenge, pups of allergic mothers had dysbiosis in lung microbial composition with increased Proteobacteria and decreased Bacteroidota and this was blocked by αT supplementation. We determined whether intratracheal transfer of pup lung dysbiotic microbial communities modifies the development of allergy in recipient pups early in life. Interestingly, transfer of dysbiotic lung microbial communities from neonates of allergic mothers to neonates of non-allergic mothers was sufficient to confer responsiveness to allergen in the recipient pups. In contrast, neonates of allergic mothers were not protected from development of allergy by transfer of donor lung microbial communities from either neonates of non-allergic mothers or neonates of αT-supplemented allergic mothers. These data suggest that the dysbiotic lung microbiota is dominant and sufficient for enhanced neonate responsiveness to allergen. Importantly, infants within the INHANCE cohort with an anti-inflammatory profile of tocopherol isoforms had an altered microbiome composition compared to infants with a pro-inflammatory profile of tocopherol isoforms. These data may inform design of future studies for approaches in the prevention or intervention in asthma and allergic disease early in life.